Pitfalls in diagnosis and treatment of alveolar echinococcosis: a sentinel case series - Stojković, Marija; Mickan, Christina; Weber, Tim; Junghanss, Thomas (BMJ open gastroenterology, 2015)
Background Alveolar echinococcosis (AE) is a neglected zoonosis presenting with focal liver lesions (FLL) with a wide range of imaging patterns resembling benign as well as malignant FLLs. Complementary serology and histopathology may be misleading. - Objective The objective of our study is to highlight pitfalls leading to wrong diagnoses and harmful interventions in patients with AE. - Design This retrospective sentinel case series analyses diagnostic and treatment data of patients with confirmed AE. - Results 80 patients treated between 1999 and 2014 were included in the study. In 26/80 patients treatment decisions were based on a wrong diagnosis. AE was mistaken for cystic echinococcosis (CE) in 12/26 patients followed by cholangiocellular carcinoma (CCA) in 5/26 patients; 61/80 patients had predominantly infiltrative liver lesions and 19/80 patients had a predominantly pseudocystic radiological presentation. Serology correctly differentiated between Echinococcus multilocularis and Echinococcus granulosus in 53/80 patients. Histopathology reports attributed the right Echinococcus species in 25/58 patients but failed to differentiate E. multilocularis from E. granulosus in 25/58 patients. Although contraindicated in AE 8/25 patients treated surgically had instillation of a protoscolicidal agent intraoperatively. One of the eight patients developed toxic cholangitis and liver failure and died 1 year after liver transplantation. - Conclusions Misclassification of AE leads to a critical delay in growth inhibiting benzimidazole treatment, surgical overtreatment and bares the risk of liver failure if protoscolicidal agents are instilled in AE pseudocysts.